SURVEY ON THE IDLE CAPACITY OF FISH PROCESSING ( FREEZING) PLANTS IN INDIA-I.WEST COAST - IYER, H KRISHNA; RAO, P SRINIVASA; UNNITHAN, G R; KESAVAN NAIR, A K; NAIR, R G (Fishery Technology, 2017)
The extent of idle capacity in fish processing (freezing) plants estimated by stratified random sampling is reported. The estimates for 1978 and 1979 for the processing plants on the west coast of India were 76.9 % and 73.2 % respectively at the rate of 250 working days per annum and two shifts per day. The percentage error of estimates worked out to 6.04 for 1978 and 6.98 for 1979. Substantial under utilization of processing plants noticed in all the states accounts mainly to the non-availability of raw material (prawn), high cost of production and shortage of power.